Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Produktivitas Kerja Pegawai Badan Kesbangpol Kabupaten Pati - Teti Safari; Ahmad Handika Ardiyani; Hesti Ristanto (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2023)
Organizations, companies or government agencies basically need individuals who are capable and have high competence in creating success for an organization. Success in achieving goals depends on choosing goals to be achieved by using resources to achieve organizational goals in accordance with what is expected. The objectives of this research include: 1). The influence of work discipline on the work productivity of Pati Regency Kesbangpol Agency employees. 2). The influence of work motivation on the work productivity of Pati Regency Kesbangpol Agency employees. 3). What is the influence of work discipline and work motivation together on the work of Pati Regency Kesbangpol Agency employees The method used in this research is quantitative research with a descriptive format aimed at explaining and summarizing various conditions, various situations, or various variables that arise in society which is the object of the research based on what is happening. The research method used in this research is the survey method. This research uses samples from the entire research population at the Pati Regency National and Political Unity Agency office. Meanwhile, data collection is through a questionnaire that uses a design from a quantitative description survey method to describe various conditions or variables that are the object and focus of research in real terms. The results in this research include: 1). Work discipline (X1), has a positive and significant effect on the work productivity of Pati Regency Kesbangpol Agency employees. 2). Work motivation (X2) has a positive and significant effect on the work productivity of Pati Regency Kesbangpol Agency employees. 3). Work discipline and work motivation together have a positive and significant effect on the work productivity of Pati Regency Kesbangpol Agency employees.